Exploring perceptions of healthcare providers' communication skill and PrEP use in men who have sex with men. Issue 4 (8th August 2021) - Schwartz, Joseph; Grimm, Josh; Zimmerman, Rick; Clement, Meredith
ABSTRACT: HIV continues to be serious issue in the U.S., especially for men who have sex with men (MSM). Pre–exposure prophylaxis (PrEP) is a highly effective means of preventing HIV, but its adoption has been slower than expected. The purpose of this study was to investigate the extent to which MSM's perceptions of their healthcare providers' level of communication skill predicted PrEP status. An online survey of 969 MSM was conducted. The results showed that respondents who perceived that their healthcare provider was skilled in information giving, information receiving, and information verifying were more likely to be on PrEP than respondents who perceived their healthcare provider had a lower level of skill in these areas. These findings highlight the importance of providers' communication skill in healthcare, particularly for MSM